Interaction and Communication in IbuSibuk Community as a Factor for Empowering Women in The Digital Era - Juan Prince Adeliant; Tangguh Okta Wibowo; Andiani Fitri Febrina; Chelsea Roxanne Ramadhane; Gabriella Christie Kartadibrata (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
This research focuses on the Ibu Sibuk community, an online community that empowers mothers to become influencers and resellers through social commerce platforms. The background of this research includes the community's goals, the platform's success in attracting members and brands, and the members' experiences in using communication technology to interact in the community. This study used a qualitative approach with a case study design to understand the role of the IbuSibuk community for women who already have a family and are mothers. The research informants consisted of two members and two administrators of IbuSibuk, who were selected through a purposive sampling technique. Data were collected through face-to-face or online interviews, literature reviews from academic journals, and website information. The research results show that IbuSibuk is an online community that helps working mothers earn extra income as influencers by connecting them with various brands. This community empowers mothers economically through the programs and activities offered but also faces technological barriers such as network and digital literacy issues and the potential for fraud. Nevertheless, technology within IbuSibuk extends its reach and facilitates offline activities such as product launches. Overall, IbuSibuk serves as a bridge between brands and influencers, empowers mothers economically, and creates a supportive and motivating environment for its members.